The influence of user-generated content (UGC) and social tagging on corporate reputation in higher education institutions (HEI) - Anuar, Aisyah Nadhirah; Saiful Bahry, Farrah Diana; Wahi Anuar, Muhammad Asyraf (Faculty of Information Management, 2025)
Higher Education Institutions (HEIs) face increasing competition in attracting students, and corporate reputation plays a vital role. This study examines the impact of user-generated content (UGC) and social tagging on the corporate reputation of Universiti Teknologi MARA (UiTM). Despite the recognized importance of social media, limited understanding exists of the specific effects of UGC and social tagging within this context. Using a state-of-the-art review, the research formulates a framework comprising UGC dimensions—corporate image, UGC quality, and UGC trust—and social tagging dimensions—tag contribution, affective social presence, and cognitive social presence. By synthesizing these factors and their interrelationships, the study aims to provide actionable insights for HEIs to enhance their corporate reputation through strategic social media engagement. The findings will guide institutions in leveraging UGC and social tagging to strengthen their reputation and achieve competitive advantages in the digital era.